Sea Ice as Enemy and Friend: The Case of Iceland and Labrador - Ogilvie, Dr. Astrid (2011)
Dr. Astrid Ogilvie, CICERO, Centre for International Climate and Environmental Research, Oslo, at the NRF 6th open Assembly in Hveragerði, Iceland. September 2011.